A Case of Choriocarcinoma Initially Diagnosed as an Ectopic Pregnancy With a Concomitant Invasive Squamous Cell Cervical Cancer [199]. (May 2015) - Martin, Laura; Chura, Justin; Goldenthal, Emily; Jaspan, David
Abstract : INTRODUCTION: We report a case of choriocarcinoma that was initially diagnosed as an ectopic pregnancy with a concomitant invasive squamous cell cervical cancer. CASE PRESENTATION: A 35-year-old woman, gravida 4 para 3, presented to an outside hospital with vaginal bleeding and pelvic pain. Diagnosed with ectopic pregnancy, the patient was brought to the operating room. Examination under anesthesia revealed a fungating cervical mass. A biopsy was obtained, but dilatation and curettage was deemed too dangerous. The patient was empirically treated with methotrexate. The gynecology team at Einstein was contacted when the cervical biopsy returned as poorly differentiated invasive squamous cell carcinoma of the cervix. The patient was taken to the operating room by a gynecologic oncologist for a staging procedure, further cervical biopsy, and a failed attempt at dilatation and curettage. Pathology showed invasive poorly differentiated carcinoma with focal areas of squamous differentiation, extensive ulceration, necrosis, and hemorrhage. The patient began chemotherapy with plans for radiation therapy. The β human chorionic gonadotropin (β-hCG) levels continued to plateau. The case was brought to the tumor board and the potential for a choriocarcinoma was then raised. The slides were reviewed and restained. With this information the diagnosis of choriocarcinoma was made. The chemotherapy was adjusted and the β-hCG began to fall. DISCUSSION: The case demonstrates the importance of trending β-hCG levels in the absence of a pathology report confirming products of conception. This case also demonstrates the importance of interdisciplinary discussion and review of cases to provide quality care.